The role of customer satisfaction in mediating the effect of experiential marketing on repurchase intention: Evidence from Klinik Kopi Yogyakarta - Wulandari, Friska Mei; Transistari, Ralina; Adiseputra, Yudhistira (Junal Ilmu Manajemen, 2025)
The relentless proliferation of coffee shops has amplified market competition, requiring a shift from product-centric to experience-centric strategies. This study investigates the direct and indirect influence of Experiential Marketing (EM) on Repurchase Intention (RI), mediated by Customer Satisfaction (CS), using data from 100 consumers of Klinik Kopi Yogyakarta. Employing a quantitative approach and path analysis, the study confirmed that EM significantly and positively affects RI (β EM→RI =0.258) and CS (β EM→CS =0.655), while CS is the dominant predictor of RI (β CS→RI=0.762). Crucially, the findings established that Customer Satisfaction fully mediates the relationship between EM and RI. This result underscores the necessity for unique experiences (EM) to be successfully converted into profound psychological satisfaction (CS) before they can sustainably drive repeat purchasing behavior. The model demonstrates high explanatory power, accounting for 92.0% of the variance in Repurchase Intention. This research contributes theoretically by validating the Expectation-Disconfirmation Theory in the unique context of specialized Indonesian coffee shops and underscores a key practical implication: for coffee shops, merely providing a unique experience (EM) is insufficient; that experience must be successfully converted into profound psychological satisfaction (CS) before it can sustainably drive repeat purchasing behavior. Managers should therefore prioritize investments in staff training and service personalization to foster emotional connection and satisfaction (CS), which is the most powerful lever for securing long-term customer loyalty and repeat visits and provides clear, actionable managerial insight into prioritizing the emotional and relational dimensions of the customer journey over purely functional product offerings." (Specific actions like staff training and service personalization are mentioned, directly linking the statistical finding (full mediation by CS) to a managerial implementation.)